2011
DOI: 10.1128/jb.00082-11
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of the Major Outer Membrane Protein Expression Locus in Anaplasma platys and Seroreactivity of a Species-Specific Antigen

Abstract: Anaplasma platys infects peripheral blood platelets and causes infectious cyclic thrombocytopenia in canines.The genes, proteins, and antigens of A. platys are largely unknown, and an antigen for serodiagnosis of A. platys has not yet been identified. In this study, we cloned the A. platys major outer membrane protein cluster, including the P44/Msp2 expression locus (p44ES/msp2ES) and outer membrane protein (OMP), using DNA isolated from the blood of four naturally infected dogs from Venezuela and Taiwan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…A single full-length p44 (msp2) locus is remarkable, as it is highly polymorphic and similar to the A. marginale msp2 expression locus (22,24,136), and it is designated p44ES (msp2ES). It was recently shown that this locus is also conserved in A. platys (121). The remaining p44 genes, including the p44 pseudogenes in the chromosome, function as donor p44 genes to recombine at p44ES to be expressed from this genomic locus as a full-length recombined protein.…”
Section: Major Surface Antigen P44mentioning
confidence: 99%
“…A single full-length p44 (msp2) locus is remarkable, as it is highly polymorphic and similar to the A. marginale msp2 expression locus (22,24,136), and it is designated p44ES (msp2ES). It was recently shown that this locus is also conserved in A. platys (121). The remaining p44 genes, including the p44 pseudogenes in the chromosome, function as donor p44 genes to recombine at p44ES to be expressed from this genomic locus as a full-length recombined protein.…”
Section: Major Surface Antigen P44mentioning
confidence: 99%
“…Compared with A. phagocytophilum and infections involving this organism, which have been vigorously studied worldwide as an important emerging disease, A. platys and the infections it causes have been studied only in endemic regions. Despite the difference between these two Anaplasma spp., the serological diagnosis of A. platys infections in dogs has relied on a commercial ELISA kit utilizing a cross-reaction by antibodies against A. phagocytophilum and A. platys [ 10 , 35 ], partly due to the unavailability of isolated A. platys culture strains [ 20 ]. However, the use of this kit against these two species may limit the ability to reveal the true presence of zoonotic anaplasmosis in areas where R. sanguineus is common [ 29 ].…”
mentioning
confidence: 99%
“…Antigenic variation, immune evasion, persistence, and transmission have been most completely studied in A. marginale and is the focus here. However, detailed studies, including complete genome sequencing, of A. phagocytophilum have supported common genetic mechanisms underlying antigenic variation (810) as have more limited studies for A. ovis and A. platys (11–12). …”
Section: Introductionmentioning
confidence: 99%